Sleep Quality, Excessive Daytime Sleepiness and Insomnia in Chilean Paralympic Athletes [Calidad del Sueno, Somnolencia E Insomnio en Deportistas Paralimpicos de Elite Chilenos] - Herrera-Valenzuela, T (Grupo Aula Medica S.A., 2015)
Introduction: the sleep takes part in diverse biological and physiological functions, associating his restriction, with minor performance in the sport, nevertheless the quantity and quality of sleep is not known in paralympic athletes. Objective: to determine the sleep quality, insomnia and excessive daytime sleepiness in Chilean paralympic athletes. Methods: descriptive transverse Study, the sample included 33 paralympic athletes (24.2% women), those who were practicing swimming, tennis of table, football 5, powerlifting and tennis chair. The studied variables measured up across two surveys of dream: the Questionnaire of Insomnia and the Pittsburgh Sleep Quality Index. Results: the paralympic athletes sleep were 6.9 } 1.4 hours, 27.7% presents daytime sleepiness, 69.6% insomnia (Survey of insomnia =7), whereas 78.7% exhibits a bad sleep quality. The age showed a positive correlation with latency to the sleep (r=0.417 *), the insomnia with latency to the sleep (r=0.462 **), the Pittsburg score was correlated negatively by the sleep duration (r =-0.323) and latency to the sleep is correlated positively by the Pittsburgh score (r=0.603 **). Conclusion: the chilean paralympic athletes, present a low sleep quality, insomnia and excessive daytime sleepiness, situation that might influence negatively the sports performance. © 2015, Grupo Aula Medica S.A. All rights reserved.